2011
DOI: 10.1088/1758-5082/3/3/034112
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinting cell-laden matrigel for radioprotection study of liver by pro-drug conversion in a dual-tissue microfluidic chip

Abstract: The objective of this paper is to introduce a novel cell printing and microfluidic system to serve as a portable ground model for the study of drug conversion and radiation protection of living liver tissue analogs. The system is applied to study behavior in ground models of space stress, particularly radiation. A microfluidic environment is engineered by two cell types to prepare an improved higher fidelity in vitro micro-liver tissue analog. Cell-laden Matrigel printing and microfluidic chips were used to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 24 publications
1
113
0
5
Order By: Relevance
“…It was demonstrated that the liver tissue retained ATP and Albumin levels as well as expression and drug-induced enzyme activity of Cytochrome P450s after 28 days post-fabrication [96]. Snyder et al [97] utilized Matrigel for printing of a liver-like tissue in a microfluidic chip for radioprotection study. In the study by Wang et al [98], it was found that the laminated hepatocytes remained viable and performed biological functions for more than 2 months.…”
Section: Bioprinting Of Livermentioning
confidence: 99%
“…It was demonstrated that the liver tissue retained ATP and Albumin levels as well as expression and drug-induced enzyme activity of Cytochrome P450s after 28 days post-fabrication [96]. Snyder et al [97] utilized Matrigel for printing of a liver-like tissue in a microfluidic chip for radioprotection study. In the study by Wang et al [98], it was found that the laminated hepatocytes remained viable and performed biological functions for more than 2 months.…”
Section: Bioprinting Of Livermentioning
confidence: 99%
“…As novel methods and technologies introduced in recent years for 3-D printing of biomaterials, promising overview of future appears to manufacture scaffolds for tissue engineering that reach the gold standards and also better comprehensions of stem cells microenvironments and interactions. By aid of various novel technologies, such as microfluidic systems [75,76], biopatterning [77], and layer-by-layer assembly [76,78], researchers are now able to biomanufacture microtissue constructs within scaffolds and even also within scaffold-free environments. Considering the great and enormous improvements of biomaterial for tissue engineering, in contrast, there are still certain challenges and difficulties that need more attention.…”
Section: Future Aspects Of 3-d Printing For Regenerative Medicinementioning
confidence: 99%
“…The dispensing system can extrude hydrogel from the nozzles, producing defined structures. The automated robotic system for extrusion printing is generally powered by either a pneumatic [62][63][64][65][66][67][68][69][70] or a mechanical pump [71,72] . These pumps act by applying a positive pressure on the hydrogel causing it to flow out of the nozzle.…”
Section: Materials Extrusionmentioning
confidence: 99%